Estudo do potencial energético nos aterros sanitários do brasil - Tavares, Rafaela de Oliveira (2018)
In the presence of current problems related to environmental preservation issues, the possibility of a shortage of natural resources in the short-term period, and the growing demand of energy need in the country, the alternative power generation through renewable sources are presented as ecologically and economically feasible solutions for such challenges. This theses aims to demonstrate the potential of energy generation in Brazil through biogas from landfills. It presents main concepts about power generation, showing the existing types of power generation, focused on generation from solid urban waste. The step by step process of treatment of the biogas until its generation of energy was corroborated through data inputs and actual information of a Thermoelectric Plant. For the potential measurement, calculation methods were developed by the IPCC (Intergovernmental Panel on Climate Change) to obtain the number of methane emissions and consequent potential biogas generation. Through the results obtained, it was possible to examine the financial viability of this generation system that contributes to the optimisation of natural resources and reduction of greenhouse gases.